2011
DOI: 10.1128/jcm.01946-10
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a Novel Shigella flexneri Serotype 4s Strain That Evolved from a Serotype X Variant in China

Abstract: This paper describes the first isolation of a new Shigella flexneri serotype, designated 4s, in Beijing, China. Genotypic and phenotypic profiling suggests that this isolate is a clone of the S. flexneri serotype X variant reference strain. Of particular concern is the multidrug resistance exhibited by this isolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
1
28
1
Order By: Relevance
“…According to a multicenter shigellosis surveillance study that incorporated data from six Asian sites, including China, shigellosis incidence is approximately 100-fold higher in Asia than in industrialized countries [5]. Other reports in China have indicated that shigellosis is even more ubiquitous than previously thought [18,19]. These studies have generally selected underdeveloped areas as surveillance sites, with little current information available on the epidemiologic trends in large cities like Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…According to a multicenter shigellosis surveillance study that incorporated data from six Asian sites, including China, shigellosis incidence is approximately 100-fold higher in Asia than in industrialized countries [5]. Other reports in China have indicated that shigellosis is even more ubiquitous than previously thought [18,19]. These studies have generally selected underdeveloped areas as surveillance sites, with little current information available on the epidemiologic trends in large cities like Beijing.…”
Section: Discussionmentioning
confidence: 99%
“…Although there had been a dramatic drop in overall infectious disease outbreaks between 1975 and 1995, it has since then reverted and maintained a gradual upward trend 5. It is reported that bacillary dysentery, one of the top four infectious diseases from 2005 to 2010, presents nearly 500 000 cases each year in China 6. In addition to high incidence rates, bacillary dysentery treatment is severely threatened by the episodic emergence of new antibiotic resistance strands 7.…”
Section: Introductionmentioning
confidence: 99%
“…One serotype in particular, S. dysenteriae serotype 1, which produces Shiga toxin, is responsible for the most severe infections, including hemolytic uremic syndrome (15), and it is the cause of epidemic dysentery. Additionally, serotypes can drift during outbreaks, further limiting the efficacy of vaccines that are restricted to particular serotypes (37,56). The emergence of strains resistant to antimicrobial drugs, including ciprofloxacin, currently the first-line antibiotic treatment against Shigella infections (20,46,55), heightens the difficulty of controlling this pathogen and makes the development of an effective vaccine even more urgent.…”
mentioning
confidence: 99%